Mouthpart and digestive tract morphology of the synchronized firefly, Pteroptyx tener (coleoptera: lampyridae) - Nurul Wahida O.; Nur Hudawiyah A.; Roslim R.; Nur Khairunnisa S.; Norela S. (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
The firefly, Pteroptyx tener (Coleoptera: Lampyridae) lives in the mangrove area and is economically valuable for ecotourism because of its unique synchronous flashing behavior. It has been observed that the adult species does not have the appearance of sucking type mouthpart morphology though it is believed that its diet depends on the plant sap. This study focused on the morphology of the mouthpart and, anatomy and histology of the digestive tract of P. tener. From gross morphology observation, P. tener has hypognathus mouthpart with a crescent-like narrow apicle mandible. Scanning Transmission Electron Microscope (STEM) image showed that P. tener has a special food canal inside its mandible that runs from the tip to the end part of the mandible. The tip of the mandible could be used as piercing equipment for P. tener to suck plant sap for feeding purposes. Morphological investigations of the digestive tract showed that this species have a small crop, large ventriculus and long intestinal tract that is suitable for a liquid feeder insect. Histological sections show that the digestive tract consist of thick muscle layer especially on the hindgut and thin epithelial layer on all parts of the gut.